The Youth Ministry Wars and the Formation of Youthworks College - Lukabyo, Ruth (2022)
Anglican Youthworks College was established in 2000, as the first college in Australia with a specialist focus on youth and children’s ministry. In this article I will discuss the factors that led to the formation of the college in Sydney and the character of the theological training that it offered. I will examine how the college was established in the context of politics in the Diocese of Sydney and debates over the best way to do youth ministry (the “youth ministry wars”). Those involved in youth ministry were concerned about poor retention of young people in the church and as a result turned against what was called attractional ministry for (what was seen as) a more biblical and theological model. I will argue that the college used a distinctive method of youth ministry education which prioritised: the Bible, critical reflection on ministry and life, and the concept of temporary community for student formation. It reflected a concern to professionalise and think critically about spiritual formation amongst children as well as youth. I will finish with some observations that maybe helpful for youth and children’s ministry today.
Keywords: critical reflection; Spiritual Formation; Discipleship; funnel; Education; Youth Ministry